2009
DOI: 10.1038/sj.bjc.6605364
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic colorectal cancer cells from patients previously treated with chemotherapy are sensitive to T-cell killing mediated by CEA/CD3-bispecific T-cell-engaging BiTE antibody

Abstract: BACKGROUND: Novel technologies to redirect T-cell killing against cancer cells are emerging. We hypothesised that metastatic human colorectal cancer (CRC) previously treated with conventional chemotherapy would be sensitive to T-cell killing mediated by carcinoembryonic antigen (CEA)/CD3-bispecific T-cell-engaging BiTE antibody (MEDI-565). METHODS: We analysed proliferation and lysis of CEA-positive (CEA þ ) CRC specimens that had survived previous systemic chemotherapy and biologic therapy to determine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 24 publications
2
59
0
Order By: Relevance
“…63 A series of studies with MEDI-565 demonstrated that the BiTE Ò antibody construct could induce patient T cells to kill metastatic CRC specimens derived from patients previously treated with conventional chemotherapy. 64 Herein we extend these initial findings by characterizing the in vitro and in vivo pharmacology of MEDI-565. Key parameters assessed in this report include the BiTE Ò antibody construct's (a) bispecific binding capacity, (b) high potency of T cell killing of CEA-expressing cells, (c) functional effects on T cells, (d) mechanism of action of T cell killing, (e) ability to induce T cell killing of CEA-expressing cells independent of CEA density, of the presence of high levels of soluble CEA, or of the mutational status of tumor cell lines, and (f) capacity to inhibit growth of CEA-expressing tumors in xenograft mouse models.…”
Section: Introductionmentioning
confidence: 72%
“…63 A series of studies with MEDI-565 demonstrated that the BiTE Ò antibody construct could induce patient T cells to kill metastatic CRC specimens derived from patients previously treated with conventional chemotherapy. 64 Herein we extend these initial findings by characterizing the in vitro and in vivo pharmacology of MEDI-565. Key parameters assessed in this report include the BiTE Ò antibody construct's (a) bispecific binding capacity, (b) high potency of T cell killing of CEA-expressing cells, (c) functional effects on T cells, (d) mechanism of action of T cell killing, (e) ability to induce T cell killing of CEA-expressing cells independent of CEA density, of the presence of high levels of soluble CEA, or of the mutational status of tumor cell lines, and (f) capacity to inhibit growth of CEA-expressing tumors in xenograft mouse models.…”
Section: Introductionmentioning
confidence: 72%
“…Other members of the BiTE-family, which are in pre-clinical or clinical studies, are specific for carcino-embryonic antigen (CEA), EpCAM, CD33, HER2/neu, EGFR and the melanoma-specific chondroitin-sulfate proteoglycan (MCSP), also called High Molecular Weight Melanoma Associated Antigen (HMW-MAA) [94][95][96][97][98][99][100]. The MCSP-reactive BiTE was less potent in in vitro cytolysis experiments than expected [94].…”
Section: Recruiting T-cells Via Cd3mentioning
confidence: 99%
“…Furthermore, a CD3/EGFR BiTE ® caused acute toxicity in cynomolgus monkeys likely due to EGFR expression in normal tissue [10]. Not surprisingly, most CD3 bispecific proteins currently in clinical trials are targeting receptors whose expression is confined to the hematopoietic lineage (CD19, CD20, CD123) [6,11,12], or receptors with exceptionally high tumor specificity, such as carcinoembryonic antigen (CEA) [13], prostate-specific membrane antigen (PSMA) [14] or MHCI-gp100 complex [15]. Thus, the applicability of T cell redirection with currently available technologies is limited to antigens with extraordinarily high tumor specificity, which impedes the application to many solid tumor types, where no antigens with comparable high specificity are available.…”
Section: Introductionmentioning
confidence: 99%